Epidemiological investigation of avian influenza in regions of Northern Greece - PAPANIKOLAOU (I. ΠΑΠΑΝΙΚΟΛΑΟΥ) J.; KOUMBATI-ARTOPIOU (Μ. ΚΟΥΜΠΑΤΗ-ΑΡΤΟΠΟΙΟΥ) M. (Journal of the Hellenic Veterinary Medical Society, 2018)
The results of an avian influenza viruses surveillance program in chicken and turkey industrial flocks, as well as in some wild birds from regions of N. Greece during 1999-2000 are presented in this paper. For this purpose, avian influenza virus isolation was attempted by inoculation of samples from chickens and wild birds into embryonated chicken eggs. The samples originated from 35-60 week-old layers and breeders with mild respiratory signs and drop in egg production. 34 wild birds (sparrows, chaffinchs, gulls), that were brought dead to the laboratory of Veterinary Research Institute of Thessaloniki, were also examined in order to investigate the cause of their death. At the same time, 720 serum samples from 30 chicken and 6 turkey flocks were examined by Agar Gel Immunodiffusion (AGID) test. During the same period and in the framework of a surveillance program for avian influenza viruses in Greece, 2580 paired serum samples from chicks were tested by AGID test. Chicks were imported from Italy, where a Highly Pathogenic Avian Influenza was in progress during 1999-2000. All virus isolation attempts and serological tests were negative.